Pelatihan Digitalisasi Data Desa bagi Perangkat Desa Condongsari untuk Mengoptimalkan Layanan Administrasi Desa - Nuning Rohmantika; Endang Yulyanti; Hana Wahyuni; Umi Pratiwi (Faculty of Engineering UNHAS, 2022)
Information technology has developed very rapidly so that it requires humans to follow the flow of information very quickly. Technological developments have affected the lives of residents, therefore in carrying out their duties the village government must follow the development of existing technology. Condongsari Village, Banyuurip District, Purworejo Regency still uses manual/conventional methods in serving the administration of the population so that the service is not optimal. One way to optimize population administration services in the era of rapid development of information technology is the digitization of village data. This study aims to conduct training to the Condongsari Village apparatus about the importance of information technology through digitizing village data to optimize village administration services. The method used is the preparation, training, and implementation stages. The subjects in this study were all members of the Condongsari Village. The results of this study are 64% of village officials strongly agree and 36% agree that digitizing village data is very helpful and makes it easier for village officials to carry out their duties to serve population administration. It is also felt by residents that through this digitization the administrative services carried out by the village government are faster, more responsive, and the information provided is very accurate.